Voluntary Behavior Modification during a Pandemic: Perceptions and Behaviors toward COVID-19 in Japan - Budianto, Firman; Nishikori, Yuichi (UI Scholars Hub, 2021)
This study examines social measures meant to stop the spread of COVID-19 in Japan, where COVID-19 control relies heavily on the voluntary compliance of citizens. We examine how the government's campaign for controlling COVID-19 is perceived by people, and how these measures influenced people’s attitudes and behavior. This paper specifically discusses how people’s perceptions regarding COVID-19 control measures temper orthodox understandings of behavior modification, such as perceived threats, and how it influences their attitude and behavior. Qualitative data collected from an online open-ended questionnaire was cross-sectionally analyzed. This study argues that high risk perception is actually just one of many triggers of behavior modification. That is, people responsive to risk perception had to match actual hazards to perceived real risk. Furthermore, popular sources of information on COVID-19, like news and social media, were found to substantially influence people’s behavior. In particular, whether campaigns were easy to understand, whether there were societal expectations for people to follow behavior modifications, and whether people thought measures were effective at preventing COVID-19 infection had a strong impact on the adoption of behavior modification. These findings thus fill in lacuna in existing scholarship concerning the rationality behind people’s decision to voluntary adopt behavior modification measures.